Analisis Program Restrukturisasi Kredit Macet Perbankan Dengan Metode Multi-Attribute Utility Theory Dan Vooting Copeland Score - Chandra Kusuma Chandra Kusuma (Jurnal Inovasi Teknik Informatika, 2018)
Bank is a financial institution that connects parties who have funds with the parties who need funds, or public funds withdrawn by the bank and then lent back to the community. Nonperforming loans are a major problem so the Bank must immediately implement the rescue with the aim of minimizing losses. The purpose of this study is how to build a computer application that can perform selection of debtor delinquent and eligible in restrukrisasi by building computer-based system applications and help system design, which can perform selection of debtor election who are delinquent installment payments and decent restructuring , by implementing the method of Multi-Attribute Utility Theory (MAUT) and Vooting Copeland Score.